Parylene C-Based, Breathable Tattoo Electrodes for High-Quality Bio-Potential Measurements - Spanu, Andrea; Mascia, Antonello; Baldazzi, Giulia; Fenech-Salerno, Benji; Torrisi, Felice; Viola, Graziana; Bonfiglio, Annalisa; Cosseddu, Piero; Pani, Danilo (Frontiers in Bioengineering and Biotechnology, 2022)
A breathable tattoo electrode for bio-potential recording based on a Parylene C nanofilm is presented in this study. The proposed approach allows for the fabrication of micro-perforated epidermal submicrometer-thick electrodes that conjugate the unobtrusiveness of Parylene C nanofilms and the very important feature of breathability. The electrodes were fully validated for electrocardiography (ECG) measurements showing performance comparable to that of conventional disposable gelled Ag/AgCl electrodes, with no visible negative effect on the skin even many hours after their application. This result introduces interesting perspectives in the field of epidermal electronics, particularly in applications where critical on-body measurements are involved.